PENGEMBANGAN GAME EDUKASI BERBASIS FLASH SEBAGAI SARANA BELAJAR SISWA PAUD ROSS (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the lack of interactive and engaging learning media for early childhood education (PAUD) students, particularly at PAUD Ross. Conventional teaching methods are considered less effective in increasing children's learning interest. Therefore, this research aims to develop a Flash-based educational game as an enjoyable and effective learning medium for students. The method used is Research and Development (R&D), which includes needs analysis, design, development, testing, and evaluation stages. The subjects of this study were students of PAUD Ross. The results show that the developed educational game has a high level of feasibility based on expert validation and user responses. Furthermore, the use of this game has been proven to increase students' learning interest and engagement in the learning process. In conclusion, Flash-based educational games can serve as an effective and innovative alternative learning media for early childhood students.